2013
DOI: 10.1177/1049909113504981
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Policies and Practices in Pediatric Skilled Nursing Facilities

Abstract: Although most children with intellectual and developmental disabilities reside in the community, a subset of children with severe intellectual disability and complex medical needs reside in pediatric skilled nursing facilities. These children have elevated mortality with end-of-life care (EOLC) routinely provided. The present study explored policies and practice in such settings by surveying administrators, nursing directors, and medical directors in facilities across the United States. In addition to EOLC pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…One study of children who died in LTC found that parents were satisfied with their child’s end-of-life care [ 114 ], and parents of children receiving LTC were found to have better reported physical health and family functioning when compared to parents of children receiving home care or medical day care [ 12 ]. LTC facilities, though, are also challenged by staffing shortages [ 114 ], limited funding [ 113 ], insufficient end-of-life care policies, and inadequate staff training [ 115 ].…”
Section: Conceptual Framework Of Home-based Care For Children With Se...mentioning
confidence: 99%
“…One study of children who died in LTC found that parents were satisfied with their child’s end-of-life care [ 114 ], and parents of children receiving LTC were found to have better reported physical health and family functioning when compared to parents of children receiving home care or medical day care [ 12 ]. LTC facilities, though, are also challenged by staffing shortages [ 114 ], limited funding [ 113 ], insufficient end-of-life care policies, and inadequate staff training [ 115 ].…”
Section: Conceptual Framework Of Home-based Care For Children With Se...mentioning
confidence: 99%
“…Recent research in the disability sector has shown that end‐of‐life care training (Friedman, Helm, & Woodman, ) and “bereavement training” may help staff identify and support service users experiencing grief. Clinicians also need to be supported in managing their own grief, and organizational policies and resources should be instituted to support the grief processes of both service users and staff (Gray & Truesdale, ; see Table .14).…”
Section: Challenges In the Delivery Of Quality Palliative And End‐of‐mentioning
confidence: 99%
“…We are unaware of any research examining the conditions under which Do not resuscitate (DNR) orders are decided and implemented with people with intellectual disability. The current literature is limited largely to ethical issues and policy commentary (Friedman, Helm, & Woodman, ; Laventhal et al., ). Important questions might include the extent to which people with intellectual disability are afforded the opportunity to make decisions about DNR, the context of decision making (including the person's capacity, family and health professional support), and the operationalization of DNR policy in community and hospital settings.…”
Section: Future Researchmentioning
confidence: 99%